MODERN TEENAGER (HIGHLANDER) AND SEX - Oksana Fedyk (Vasyl Stefanyk Precarpathian National University, 2015)
The age at which you can start or be sexually active - a very interesting question, which concerned not only parents, but also psychologists. Usually, you can not answer the question of when and to whom to start having sex. However, there are certain statistics that the average age of sexual debut in adolescents - is 15 years for girls and 14 for boys. Now we are talking about European society, about what is happening in Ukraine, particularly in mountainous areas. The fact that the willingness in principle to sexual intercourse is associated with physiological aspects. There is a notion in sexology - sexual constitution. There are several factors play a role, of course, one of which is constitutional, but not always, psychological maturity and sexual constitution, rather, because of the need for sexual constitution in holding intercourse can match. That is, some teens may be physiologically ready for sexual intercourse at 12-13 years, but the question arises: Are they psychologically? And probably we can not give a definite answer to this question, because curiosity taboo in society, which in the majority rejects teen sex, pushing them into early sexual relations. Nevertheless, probably still age readiness and psychological and physiological - is 18-19 years if we are talking about teen sex.